(untitled) (International Journal of Communication Systems and Network Technologies, 2023)
The copyright for content protection and authentication are the two main important criterion of any digital image watermarking. Any watermarking scheme are four major requirements of security, higher imperceptibility, robustness, and large capacity. Focussing on the requirements this paper presents a novel image watermarking scheme using random discrete fractional fourier transform (RDFRFT) with multiple parameter discrete fractional Fourier transform (MPDFRFT). The system uses the RDFRFT to convert original image into fractional fourier domain and embed the watermark image in the original image using MPDFRFT. The MPDFRFT is used to enhance security of the watermarked image by setting multiple parameters as a key. The multiple-parameter discrete fractional Fourier transform (MPDFRFT) is N order DFRFT parameters, where N refers to the number of the input data points. The MPDFRFT posses to have all of the desired properties for fractional transforms. The MPDFRFT reduces to the DFRFT when all of its order parameters are having the same value whereas RDFRFT is kernel matrix with random DFT eigenvectors and eigenvalues. The RDFRFT has key feature that the phase and magnitude of its transform output are both random so this feature has been utilized for enhancing the security. The proposed scheme is implemented by subdividing the cover image and RDFRFT is applied on each subdivided image to transformed coefficients then MPDFRFT is applied on watermark image with different parameters for enhancing the robustness. Similarly, during watermark extraction process the reverse order of MPDFRFT and inverse of RDFRFT is applied for reconstruction of original images and watermark image. The robustness of the watermark image is examined under various attacks such as rotation, additive noise, cropping and filtering operations. The analyzed and simulation results validates that the embedding scheme has good performance of major watermarking parameters robustness and perceptibility.